2022
DOI: 10.1002/pros.24370
|View full text |Cite
|
Sign up to set email alerts
|

Orphan receptors in prostate cancer

Abstract: Background: The identification of new cellular receptors has been increasing rapidly.A receptor is called "orphan" if an endogenous ligand has not been identified yet.Methods: Here we review receptors that contribute to prostate cancer and are considered orphan or partially orphan. This means that the full spectrum of their endogenous ligands remains unknown. Results:The orphan receptors are divided into two major families. The first group includes G protein-coupled receptors. Most are orphan olfactory recepto… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 107 publications
(318 reference statements)
0
3
0
Order By: Relevance
“…The RORA gene or also called NR1F1 (nuclear receptor subfamily 1, group F, member 1) is a transcription factor that plays a critical role in the regulation of various biological processes, including circadian rhythm, metabolism, and inflammation [ 31 ]. Recent studies have suggested that RORA may also be involved in PCa progression [ 32 ], even a RORA polymorphism rs17191414 has been associated with PCa risk, however, this data needs to be validated in other cohorts [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The RORA gene or also called NR1F1 (nuclear receptor subfamily 1, group F, member 1) is a transcription factor that plays a critical role in the regulation of various biological processes, including circadian rhythm, metabolism, and inflammation [ 31 ]. Recent studies have suggested that RORA may also be involved in PCa progression [ 32 ], even a RORA polymorphism rs17191414 has been associated with PCa risk, however, this data needs to be validated in other cohorts [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is known that their overexpression inhibits cell proliferation and promotes cell death. Additionally, OR51E2 inhibits the growth of prostate cancer but promotes invasiveness and metastasis [ 7 , 8 ]. However, no report to date has explored the potential application of extranasal OR for diagnosis or its “druggability” in human diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, it was noticed that the OR transcripts identified in nonolfactory tissues were not a mere representation of those present in the olfactory epithelium but a subset of the ORs encoded in the genome; even more interestingly, different subsets were identified in different tissues. Later on it was shown that the activation of OR in colorectal cells lead to inhibition of cell proliferation and apoptosis [9], and that OR play in blood pressure regulation [10] or the implication of OR 51B5 in myolenous leukemias cells [11] and more [12,13].…”
Section: Introductionmentioning
confidence: 99%